2001
DOI: 10.1007/pl00001360
|View full text |Cite
|
Sign up to set email alerts
|

Changes in photosynthetic properties measured by oxygen evolution and variable chlorophyll fluorescence in a simulated entrainment experiment with the cyanobacterium Planktothrix rubescens

Abstract: The metalimnion of lake Zürich is dominated by the red coloured cyanobacterium Planktotrix rubescens, where it lives in an extremely low light environment. Photosynthesis of the organism was studied using oxygen evolution and variable fluorescence. After transfer to 2 m depth in the epilimnion, simulating an entrainment event that normally occurs in late summer, photoacclimation was followed.The metalimnetic population had a very high photosynthetic efficiency, and the minimum quantum requirement varied betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Cell weight/number cells (mg DW10 6 cells -1 ), cell weight/culture volume (mg DW L -1 ),electron transport rate (ETR, µmol e -m -2 s -1 ), average measured (mBP) and average estimated (eBP) biomass productivity expressed as g DW m -2 day -1 , photosynthetic efficiency as mBP per mol photons absorbed (%) and specific absorption coefficient (Kc, m 2 mg Chl-a Photosynthetic efficiency (%) 2.11 ± 0.35 1.63 ± 0.18 overestimation is rather constant, despite considerable changes in phytoplankton composition. Spectral correction of fluorescence data caused a reduction of 30% or an increase of 44% in the estimated Cfixation, depending how C-fixation was estimated (Kromkamp et al, 2001). In this study with C. fusca, less deviation among estimated and measured biomass yield than that between carbon fixation and ETR reported by Kromkamp et al (2001) in other species was found.…”
Section: Estimation Of Carbon Production By Using Chlorophyll Fluoresmentioning
confidence: 47%
See 1 more Smart Citation
“…Cell weight/number cells (mg DW10 6 cells -1 ), cell weight/culture volume (mg DW L -1 ),electron transport rate (ETR, µmol e -m -2 s -1 ), average measured (mBP) and average estimated (eBP) biomass productivity expressed as g DW m -2 day -1 , photosynthetic efficiency as mBP per mol photons absorbed (%) and specific absorption coefficient (Kc, m 2 mg Chl-a Photosynthetic efficiency (%) 2.11 ± 0.35 1.63 ± 0.18 overestimation is rather constant, despite considerable changes in phytoplankton composition. Spectral correction of fluorescence data caused a reduction of 30% or an increase of 44% in the estimated Cfixation, depending how C-fixation was estimated (Kromkamp et al, 2001). In this study with C. fusca, less deviation among estimated and measured biomass yield than that between carbon fixation and ETR reported by Kromkamp et al (2001) in other species was found.…”
Section: Estimation Of Carbon Production By Using Chlorophyll Fluoresmentioning
confidence: 47%
“…Spectral correction of fluorescence data caused a reduction of 30% or an increase of 44% in the estimated Cfixation, depending how C-fixation was estimated (Kromkamp et al, 2001). In this study with C. fusca, less deviation among estimated and measured biomass yield than that between carbon fixation and ETR reported by Kromkamp et al (2001) in other species was found. Linear relation between estimated and measured biomass productivity has been determined in Chlorella sp.…”
Section: Estimation Of Carbon Production By Using Chlorophyll Fluoresmentioning
confidence: 47%
“…These values most probably underestimate the efficiency of PS II. As Kromkamp et al (2001) point out, thylakoids of cyanobacteria are also used for respiration and phycobilisomes produce fluorescence both leading to underestimations of F v /F m . The functional absorption cross section (r PSII ) was higher during stratification and also showed a distinct vertical pattern.…”
Section: Mondsee Is a Deep Oligotrophic Alpine Lake With A Seasonal Pmentioning
confidence: 99%
“…In the metalimnion (10-12 m) where P. rubescens by far dominates the phytoplankton assemblage in summer, F v /F m was 0.39-0.44. These values most probably underestimate the efficiency of PSII because of alternative electron sinks: (1) thylakoids of cyanobacteria are also used for respiration, and (2) phycobilisomes can produce fluorescence (Kromkamp et al, 2001).…”
Section: Physiological Approachmentioning
confidence: 99%